Lusos & Caetés - Castello, José Aderaldo (Revista do Instituto de Estudos Brasileiros, 1993)
Caetés presents a case of adultery in a small town, but its fundament is the self-portrait of the protagonist-narrator projected in national representation. Here Graciliano Ramos distinguishes himself from this model, Eça de Queiróz´s A Ilustre Casa de Ramires, by virtue of recourse to the first person for the present action, action in which the project of historical narrative is diluted by use of the third person. This account, also imbued with formal reflection, lays the foundations for the confrontation of the past and the contemporary. Aspects of the national characteristic are delineated, coinciding with proceedings of the 1920´s.